Design and Modelling of a 2W MMIC Ku-band Power Amplifier for TT&C Transmitters - Backefelt, Lars; Özcelik, Aykut (My University, 2014)
The Telemetry, Tracking and Command, TT&C, communication subsystem is the lifeline of a satellite and is a way to remotely monitor its status. The subsystem can confirm position and angle in relation to the base station as well as make small adjustments to its orbit if needed. The system constantly receives and transmits information and is active from launch to the end of the life cycle where the data is sent by the telemetry transmitter using phase modulation. In order to minimize power consumption and to ensure a reliable operation of the TT&C subsystem, the output amplifier of the telemetry transmitter must be designed with great care. As collaboration between Chalmers University of Technology and Kongsberg Norspace, the aim of the thesis was to design a 2W MMIC power amplifier as well as measuring important parameters of a commercial equivalent to use as a benchmark. By investigating different topologies and techniques the amplifier size and channel temperatures were kept down while the design achieved the desired output power. Various processes and bias points were reviewed before selecting PPH25X from UMS as a base for the MMIC design. PPH25X is a space qualified process using pHEMT transistors that possess high power density to ensure the wanted output power. The simulated amplifier uses three stages with 14 active devices in total to keep the temperature down in the output stage. Different techniques were used to make the active devices stable and to achieve a flat gain throughout the band. The final design achieved a P1 dB of 33.3 ± 0.3dBm with a gain and gain variations of 25.4 dB and 0.45 dB/500MHz respectively, at a maximum channel temperature of 95 deg C.
Keywords: Elektroteknik och elektronik; Informations- och kommunikationsteknik; Kommunikationssystem; Electrical Engineering, Electronic Engineering, Information Engineering; Information & Communication Technology; Communication Systems